Caricature drawing and its impact on learning expressive drawing (educational units) (Journal of the College of Basic Education, 2022)
Caricature drawing is one of the fields of plastic arts that have not been dealt with or accessed to its details or invested in the field of art education at the university level. One of the ways of individualizing education is that it may be commensurate with learning the skill of drawing, in a way that encourages the student to learn on his own, as well as what generates impulsiveness and competition with the rest of his peers.